Answer:
60.4%
Step-by-step explanation:
Initial cost = $240,000
profit of first year = $65,000
this is reduced subsequently until it reaches zero
Note that this value reduces in an arithmetic progression from $65,000 , $60,000, ... , 0
the first term A1 = 65,000
the common difference d is 60,000 - 65,000 = -5000
the last term is An = 0
we calculate for number of terms
An = A1 + (n - 1)d
0 = 65,000 + (n - 1)(-5000)
0 = 65,000 - 5000n +5000
5000n = 70,000
n = 14
using the equation for summation of terms in an arithmetic progression Sn, we solve as
Sn =
[2A1 + (n - 1)d]
Sn =
[2(60,000) + (14 - 1)(-5000)]
Sn = 7[120,000 - 65,000]
Sn = 7 x 55,000
Sn = $385,000. This is the total profit on the mine
rate of return = (385,000 - 240,000)/240,000 = 145,000/240,000 = 0.604
i.e 60.4%